Identification of FGF receptor-binding peptides for cancer gene therapy - Maruta, F; Parker, AL; Fisher, KD; Hallissey, MT; Ismail, T; Rowlands, DC; Chandler, LA; Kerr, DJ; Seymour, LW (Springer Nature, 2002)
Linear FGF receptor-binding heptapeptides were identified by phage display using sequential rounds of biopanning against cells with displacement of phage by FGF2. The consensus motif MXXP was iterated after four to five rounds and the peptide MQLPLAT was studied in depth. Phage bearing MQLPLAT showed high levels of binding to FGF receptor positive cells, with over 90% of phage bound being eluted competitively by adding free FGF2. MQLPLAT phage showed only limited binding to Cos7 cells deficient in receptors for FGF. MQLPLAT phage bound to SKOV3 cells with a Kd of 2.51×10−10 M. Although binding could be blocked by preincubation with free FGF2, heparin could not displace the phage. Use of MQLPLAT to target polyelectrolyte gene delivery vectors in vitro in the presence of serum achieved up to 40-fold greater transgene transduction than nontargeted vectors. MQLPLAT phage were administered into gastric carcinomas via the tumor-feeding artery immediately following resection from patients. The phage showed up to 9-fold more accumulation in the tumor than in adjacent regions of normal tissue, whereas control phage showed less than 2-fold. These peptides should provide useful ligands for specific delivery of gene therapy vectors to clinically relevant targets.